FAKTOR- FAKTOR YANG MEMPENGARUHI MINAT BELI DI ONLINE SHOP SPECIALIS GUESS - Petra Surya Mega Wijaya; Christina Teguh (Fakultas Bisnis UKDW, 2012)
Consumers today are familiar with online media buying. Online buying interest arises due tovarious factors, including the product factor, price, promotion, easy way transaction, andconsumer’s trust to the online seller. This research aimed to analyze the influence of theindependent variables (product, price, promotion, ease of purchase, trust) on dependentvariables (buying interest) on the online shop specialis guess. The data was obtained byobservation, by spreading 100 questionnaires to 100 women respondents who had seen theonline shop specialis guess’ promotion through Facebook media. Based on the multiplelinear regression, the results showed that price, promotion, and trust influenced the buyinginterest in the online shop Specialis Guess, while the variable products and ease of purchasedidn’t affect the interest of online purchases.Keywords: product, price, promotion, ease of purchase, trust, online shop interest